'They are your testimony': Professionals, clients and the creation of client capture during professional career progression. Issue 1 (January 2018) - Gustafsson, Stefanie; Swart, Juani; Kinnie, Nick
The relationship between professionals and clients has received considerable interest, more recently through the concept of client capture. However, little is known to date about the mechanisms through which professionals become captured by their clients. Drawing on 50 interviews investigating the promotion of lawyers to partnership in seven UK law firms, we contribute to existing understanding by exploring the creation of client capture during professional career progression. We propose that by bestowing clients with influence over who gets promoted to partnership, lawyers lose professional independence in defining the future of their firm. In addition, we illustrate how lawyers make themselves indirectly dependent on their clients by perceiving partnership as influential to client work. By doing so, they rely on their clients to legitimize partnership as the ideal career path. Based on our findings, we argue that career progression acts as an enabling mechanism for the creation of client capture as, by succumbing to the desire to advance their careers, professionals also become prone to client capture. We discuss the implications of our findings for professional–client relations and client capture, professional careers and the changing nature of professional work.